Anticipated prospects and civilian applications of Indian satellite navigation services in Sri Lanka - I.P. Senanayake (Egyptian Journal of Remote Sensing and Space Sciences, 2013)
The government of Sri Lanka has embarked on a massive development programme of the country in all spheres of the economy, with the conclusion of war in May 2009. Sri Lanka is witnessing a new era with a rapid increase especially in infrastructure development projects. With the annihilation of the threats of terrorism, new prospects in satellite and space related technologies and their applications are flourishing. Navigation satellite (NAVSAT) technology plays the core role in a majority of the modern location based services (LBS) and consequent applications can be productively utilized for the development of the country. Global Positioning System (GPS) technology and related services are currently utilized in numerous location based applications in the country. India has launched navigation service providing satellite programmes, including a regional navigational satellite system. Whilst being covered under the footprint of Indian navigational satellite programmes, neighbouring countries of India can positively use their services for the benefit of the country through collaborative approaches. In this paper, positive impacts of 3 Indian Navigational Satellite programmes (GAGAN, IRNSS and INSAT-MSS reporting system) for the civilian applications over Sri Lanka are discussed. Other neighbouring countries covered under the footprint of Indian navigational satellite programmes can also employ these services for the location based applications productively.